2010
DOI: 10.1123/ijsnem.20.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoephedrine Ingestion and Cycling Time-Trial Performance

Abstract: The aim of the current study was to investigate the effect of 180 mg of pseudoephedrine (PSE) on cycling time-trial (TT) performance. Six well-trained male cyclists and triathletes (age 33 +/- 2 yr, mass 81 +/- 8 kg, height 182.0 +/- 6.7 cm, VO2max 56.8 +/- 6.8 ml x kg(-1) x min(-1); M +/- SD) underwent 2 performance trials in which they completed a 25-min variable-intensity (50-90% maximal aerobic power) warm-up, followed by a cycling TT in which they completed a fixed amount of work (7 kJ/kg body mass) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…24 25 These three studies used a supratherapeutic dose of at least 180 mg or 2.5 mg/kg of PSE, whereas the other studies used a therapeutic dose (60–120 mg or 1–2 mg/kg). The studies that used lower dosage of PSE showed no significant improvement for all measured parameters 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 25 These three studies used a supratherapeutic dose of at least 180 mg or 2.5 mg/kg of PSE, whereas the other studies used a therapeutic dose (60–120 mg or 1–2 mg/kg). The studies that used lower dosage of PSE showed no significant improvement for all measured parameters 18…”
Section: Resultsmentioning
confidence: 99%
“…For instance, though Pritchard-Peschek et al 25 and Hodges et al 24 showed significant improvements in timed trials using PSE doses ≥180 mg or 2.5 mg/kg, the studies could not be meta-analysed as their interventions were different (1500 run25 and 7 kJ/kg body mass work24 time to completion, respectively). Owing to such heterogeneity, using the qualitative method of synthesising the evidence was more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Factor specific to the event that alter performance include monetary reward (Cabanac, 1986), prior knowledge of the exercise end-point (Ansley et al, 2004a,b; Wittekind et al, 2011), and the presence of competitors (Wilmore, 1968) especially if they are of similar ability (Corbett et al, 2012). A number of chemical agents including the stimulants – amphetamine (Swart et al, 2009b), caffeine (Del et al, 2008; Foad et al, 2008; Hogervorst et al, 2008), pseudoephedrine (Gill et al, 2000; Hodges et al, 2006; Pritchard-Peschek et al, 2010), modafinil (Jacobs and Bell, 2004), and the dopamine/noradrenaline reuptake inhibitor bupropion (Roelands et al, 2008; Roelands and Meeusen, 2010; Watson et al, 2010) – as well as the analgesic, acetaminophen (Mauger et al, 2010), or the analgesic naloxone (Surbey et al, 1984; Sgherza et al, 2002), or the cytokines interleukin-6 (IL-6; Robson-Ansley et al, 2004), or brain IL-1β (Carmichael et al, 2006) have all been shown to alter exercise performance as do placebos (Clark et al, 2000; Benedetti et al, 2007; Pollo et al, 2008; Trojian and Beedie, 2008). Psychological skills training (Barwood et al, 2008) or pre-exercise whole body cooling (Booth et al, 1997) can also improve subsequent exercise performance.…”
Section: The Central Governor Model Of Exercise Regulationmentioning
confidence: 99%
“…Although PSE use is remarkably widespread in competitive sport, the ergogenic effect of PSE is not as well documented as that of other legal (e.g., caffeine (Graham & Spriet, ; Pallarés et al., ) or banned stimulant substances (e.g., ephedrine and methamphetamine; Graham, ; Jacobs et al., ). Most of the studies with PSE have tested its ergogenic effect on endurance performance, reporting contradictory results with either positive (Hodges et al., ; Pritchard‐Peschek et al., ) or inconclusive findings (Gillies et al., ; Betteridge & Stannard, ; Berry & Wagner, ; Pritchard‐Peschek et al., ). The available studies are quite different in their experimental design, which may be the cause of the lack of agreement among them.…”
mentioning
confidence: 99%